Evaluation of the Papermaking Qualities of Mangrove Species of Andaman and Nicobar Islands - Dhawan, Rita; Karira, B. G.; Singh, S. V. (Indian Forester, 1985)
In this paper, papermaking qualities of three mangrove species viz. Heritiera Nitoralis, Bruquiera conjugata and Rhizephora mucronota of Andaman and Nicobar islands have been evaluated. The results indicate that unbleached kraft pulps(44.68 5 yield) suitable for wrapping papers could be obtained from all the three species. The unbleached pulps(kappa number 25Â±1) could be easily bleached to a brightness of 74Â±1(Elrepho) using CEH sequence and by applying 9.0% total chloride. The bleached craft from all the three species were found to possess satisfactory strength properties for making writing and printing papers.